Southeast Asias economic crisis origins, lessons, and the way forward (ISEAS, 1999)
o. Southeast Asia is suddenly in crisis, the largest country - Indonesia - deeply so. This volume, comprising a set of specially commissioned papers, examines the origins, lessons, and future path of the crisis. Why didn?́?t economists foresee the sudden and catastrophic events of 1997-98? How can seemingly robust and vigorous economies fall so far, so swiftly? Do we, in consequence, need to change the way we view the world? Is there anything to salvage of the "East Asian miracle"? Is Southeast Asia about to experience its own version of the "lost decade", analogous to that which afflicted much of Africa and Latin America in the 19